Synthetic biology & metabolic engineering of Clostridium pasteurianum - Ortega, David (2020)
Clostridia are a class of anaerobic bacteria with exquisite metabolisms and which have the potential to be exploited for production of industrial chemicals and biofuels. The advancements in genetic tools available are allowing for applying modern synthetic biology and metabolic engineering techniques to be applied for the development of industrially relevant recombinant strains of non-model organisms. One such organism is Clostridium pasteurianum, which can naturally ferment glycerol – a waste by product of the biodiesel industry – and produce the biofuel butanol and the industrial chemical 1,3-propanediol (1,3-PDO). In this thesis, a strain of C. pasteurianum with increased transformation efficiency (TE) is developed through successive deletion of host restriction modification (RM) systems. C. pasteurianum was also engineered to produce a non-natural product for the first time. Co-production of 1,3-PDO and the platform chemical 3-hydroxypropionic acid (3-HP) is achieved by introduction of two heterologous 3-HP pathways, a CoA-dependent and CoA-independent 3-HP pathway. A native glycerol inducible promoter is characterised and shown to have strong level of expression and induction and is utilised for overexpression of key enzymes in the 3-HP pathways. Using metabolic engineering, host metabolism is engineered to redirect carbon flux towards product pathways. We report the deletion of glycerol dehydrogenase (dhaD), dihydroxyacetone kinase (dhaK) and the active thiolase (thl) enzymes, confirming their roles in host metabolism and resulting fermentation phenotypes. Both 3-HP pathways are introduced into resulting mutants for improved product yield of 3-HP and 1,3-PDO. Final strains are then subject to process optimisation to evaluate the effects of pH on product formation. The best performing strains produced 66.6 moles of 3-HP and 1,3-PDO per 100 moles of glycerol compared to 11.4 moles of product in the wildtype. Lastly, a strain of C. pasteurianum was developed for efficient whole cell biocatalysis of chiral alcohols. By introducing a (R)-dependent alcohol dehydrogenase (Adh), we demonstrate high conversion of acetophenone to (R)-1-phenylethanol and high enantiomeric excess (ee). Expression of the Adh in ΔthlA2 resulted in increased substrate concentrations and conversion percentages. This thesis furthers our understanding of production of non-natural products within anaerobic systems and promotes the industrial relevance of C. pasteurianum.